1994
DOI: 10.1017/s0007123400009789
|View full text |Cite
|
Sign up to set email alerts
|

Political Values in Russia, Ukraine and Lithuania: Sources and Implications for Democracy

Abstract: Employing data from three surveys of mass opinion conducted in Lithuania, Ukraine and European Russia during 1990, 1991 and 1992, we examine three prominent but competing hypotheses about the source of political values in the post-Soviet societies: historically derived political culture, regime indoctrination and the effects of societal modernization. The literature on Soviet political culture argues that Russian mass values are distinguished by authoritarianism and love of order, values which will be largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(41 citation statements)
references
References 29 publications
2
35
0
4
Order By: Relevance
“…On the question of a strong leader, the data here confirm findings by other scholars (Reisinger, et al, 1994) that…”
Section: Scaled Economic Assessment (Itemssupporting
confidence: 91%
See 1 more Smart Citation
“…On the question of a strong leader, the data here confirm findings by other scholars (Reisinger, et al, 1994) that…”
Section: Scaled Economic Assessment (Itemssupporting
confidence: 91%
“…My own findings (Hahn, 1991) based on research in Yaroslavl' in 1990 suggested that attitudes, values, and beliefs about democracy among Russians were not altogether different from what was found in other industrialised democracies, including the USA. Generally speaking, these findings were independently confirmed in a number of other studies (Gibson, et al, 1992;Reisinger et al, 1994;Gibson, 1996) based on survey research conducted in the early 1990s.…”
Section: Literature Reviewsupporting
confidence: 67%
“…De fato, embora exista na literatura internacional um número razoável de escalas construídas para avaliar o posicionamento dos indivíduos em relação à democracia (Finkel & cols., 1999), os parâmetros psicométricos desses instrumentos são questionáveis. Nesse sentido, a maioria dos instrumentos sobre atitudes democráticas não apresenta indicadores de validade e fidedignidade, tais como a Escala de Princípios Fundamentais da Democracia (Prothro & Grigg, 1960), a Escala de Aplicação dos Princípios Democráticos (McClosky, 1964) e o Índice de Orientação Pró-Democracia (Miller, Hesli & Reisinger, 1995;Reisinger, Miller, Hesli & Maher, 1994). Mesmo quando os instrumentos mostram algum grau de validade, não apresentam indicadores confiáveis de fidedignidade, como a Escala de Adesão à Democracia (Weil, 1989(Weil, , 1993), a escala de Atitudes em Frente à Democracia (Whitefield & Evans, 1996) e a escala de Adesão aos Princí-pios Democráticos (Kaase, 1971 (Gibson, Duch & Tedin, 1992).…”
Section: Influência Dos Sistemas De Valores Nas Atitudes Políticas: Eunclassified
“…For virtually all ethnic Lithuanians in Lithuania, the resulting incorporation into the Soviet Union was illegitimate. When protest became possible in the late 1980s, citizens of the Baltic 7For an investigation of this question with regard to political values, see Reisinger et al (1994). republics, including Lithuania, were quicker to form into popular front organizations and push for an end to communist rule. Similar organizations emerged in Russia and Ukraine, but somewhat later and with less popular support.…”
Section: Cross-national and Over-time Patternsmentioning
confidence: 99%
“…That is, as Soviet citizens became politically socialized during this era, did virtually none of them gain the psychological disposition toward activity that should have been expected of a reasonable sized minority in an urbanized, industrial country such as the USSR? Or, alternatively, IODebates over the degree and direction of value change among Soviet citizens as well as over the reasons behind it continue (Bahry 1993;Gibson, Duch, and Tedin 1992;Hahn 1991;Reisinger et al 1994;Remington 1990). was the size of the segment psychologically disposed toward political activity roughly comparable to that found in other developed countries without that disposition translating into political behavior? Before Gorbachev coming to power in 1985, the Soviet regime was outwardly united in its opposition to public criticism of its policies and willing to repress those who publicly dissented.…”
Section: Political Change In Post-soviet States 957mentioning
confidence: 99%